Analysis of Kenaf Farmer’s Satisfaction With Conventional Fiber Machine - Desrina Yusi Irawati; Elisabet Junita; Agrienta Bellanov (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
The Kenaf plant is a multipurpose plant because the application of its bark in the industry is very high. Indonesia has the largest kenaf plantation in Laren, Lamongan, East Java. The kenaf farmer group in Laren has used a conventional fiber machine to assist in slicing the kenaf stalks. Conventional fiber machine operated by hand. However, the fiber machine is not a priority for farmers to do weeding because the device still has many shortcomings. Therefore, it is necessary to assess the satisfaction of the kenaf farmers with the tool. This study uses the IPA-Kano method to analyze the design attributes of the conventional fiber machine to improve the quality attributes. It determines its user's performance, expectations, satisfaction, and dissatisfaction. According to the integration analysis of the IPA-Kano method, the conventional fiber machine needs to have a more robust frame, better support for the kenaf rods, the ability to leave a small amount of fiber in the kenaf sticks, good ergonomics, the ability to change the height, less fiber left at the cracker joint, and better cracker settings.